Experiential marketing influence on Customer Loyalty Behavior (CLB) of the hotel industry in Iran: Evaluating the mediating effects of relationship quality and customer delight / Bahareh Sadat Hosseini - Hosseini, Bahareh Sadat (Institute of Graduate Studies, UiTM, 2018)
This study aims to investigate the influence of experiential marketing on the notion of Customer Loyalty Behavior (CLB) of hotels in Iran. Customer Loyalty Behavior (CLB) is a priority for marketers especially in the hospitality industry as positive experiences that customers go through are likely to lead to revisit intention. Numerous past studies on Customer Loyalty Behavior (CLB) are based on the enterprises' and businesses' viewpoints. In this study, the view point of the customers or hotel guests are taken into consideration using the dimensions of loyalty, revisit intention and word of mouth (WOM) communication as measures. This study addresses the influence of Experiential Marketing (EM) on Customer Loyalty Behavior (CLB) from the perspectives of hotel guests in the three main cities of Iran; Tehran, Isfahan and Mashhad. In addition, the mediating effects of Relationship Quality (RQ) and Customer Delight (CD) was also introduced in the study as both these variables are deemed important in the context of service provision in the hospitality industry. Customer Delight (CD) was considered more appropriate to describe the extent of satisfaction in the hospitality industry as the element of surprise is incorporated in satisfying customers. Relationship Quality (RQ) was also measured to determine the importance of establishing trustful and satisfying relationships…